Incisional Biopsy Technique Is Associated With Decreased Overall Survival for Cutaneous Melanoma. Issue 5 (15th May 2022) - Liszewski, Walter; Stewart, Jacob R.; Vidal, Nahid Y.; Demer, Addison M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Previous studies examining melanoma biopsy technique have not demonstrated an effect on overall survival. OBJECTIVE: To examine overall survival of patients with cutaneous melanoma diagnosed by shave, punch, incisional, or excisional techniques from the National Cancer Database (NCDB). MATERIALS AND METHODS: Melanoma data from the 2004 to 2016 NCDB data set were analyzed. A Cox proportional hazards model was constructed to assess the risk of 5-year all-cause mortality. RESULTS: In total, 42, 272 cases of melanoma were reviewed, with 27, 899 (66%) diagnosed by shave biopsy, 8, 823 (20.9%) by punch biopsy, and 5, 550 (13.1%) by incisional biopsy. Both the univariate and multivariate analyses demonstrated that tumors diagnosed by incisional biopsy had significantly ( p = .001) lower overall 5-year survival compared with shave techniques (hazard ratio [HR] = 1.140, 95% confidence interval [CI] 1.055 to 1.231). We found no difference ( p = .109) between shave and punch biopsy techniques (HR 1.062, 95% CI 0.987–1.142) or between punch and incisional techniques (HR 1.074, 95% CI 0.979–1.177, p = .131). CONCLUSION: Incisional biopsies were associated with decreased overall 5-year survival in the NCDB. No difference was observed between shave and punch biopsy techniques. These findings support current melanoma management guidelines.